Preparation of ZnO/CdS/BC Photocatalyst Hybrid Fiber and Research of Its Photocatalytic Properties - Beibei Dai; Cheng Chao; Xiaoyu Lu; Qingcheng Xia; Jing Han; Fei Mao; Jiazhi Yang; Dongping Sun (Journal of Nanotechnology)
An environment-friendly biomaterial bacterial cellulose (BC) is introduced to substitute general organic polymers to assist the preparation of ZnO/CdS/BC photocatalyst hybrid nanofiber through coprecipitation method under the low-temperature condition. The XRD, XPS, and SEM results show that high load of ZnO/CdS/BC ternary hybrid fiber can be produced. TGA curves scan shows that ZnO/CdS/BC hybrid fiber has better thermal properties than bacterial cellulose. The UV-Vis spectra of the ZnO/CdS/BC hybrid nanofiber (0, 10, 20, and 50 wt%, resp.) show that photocatalytic activities of ZnO/CdS/BC are influenced by the added amount of CdS. The degradation curve of methyl shows that ZnO/CdS/BC nanohybrid fibers exhibit excellent photocatalytic efficiency.